Legal reflections on the case of genome-edited babies - Shuang Liu (BMC, 2020)
Abstract Human genome-editing is banned by guidelines, laws and regulations in most countries. However, the first criminal case on genome-edited babies was sentenced in China in 2019. In this commentary we discuss our legal reflections on this case. Genome-editing on healthy embryos of human may lead to irreversible mutations and serious consequences on the heredity of future generations, while its long-term safety is unpredictable. A full set of laws, regulations along with the guidelines should be formulated to penalize genome-editing behaviors and prevent similar negative events in the future. More effective and binding mechanisms should be constructed and implemented among different countries. A collaborative network should be strengthened for better global registry and surveillance of human genome-editing technologies and research.